Optical water quality variables (Secchi depth and Forel-Ule color indexes) observed during RV SENCKENBERG cruises SE202011-1, SE202103-1, SE202206-1, SE202208-1 and RV OTZUM cruise OT202103-1 - Michelle Albinus; Axel Braun; Jens-Martin Herold; Michaela Gerriets; Anna-Lena Geßner; Helge-Ansgar Giebel; Lars Meyer-Hagg; Jens Meyerjürgens; Claudia Thölen; Jochen Wollschläger; Thomas Henry Badewien (PANGAEA, 2025)
Water clarity and color were observed during the RV SENCKENBERG cruises SE202011-1, SE202103-1, SE202206-1, SE202208-1 and RV OTZUM cruise OT202103-1 using a white Secchi disc with a diameter of 40 cm and a Forel-Ule color scale. The Secchi depth (SD) was recorded as a relative measure of water clarity at each in situ station during day time. At half SD the apparent color of the water above the submerged Secchi disc was determined using the Forel-Ule color scale. A Forel-Ule color scale is a classic tools used to differentiate the percieved color of water based on a scale from 1 (indigo blue) to 21 (cola brown). The measurements were conducted as recemmend in literature (Garaba and Zielinski, 2015; Wernand, 2011; Wernand and van der Woerd, 2010).